Unravelling metabolomics and antioxidant potential of sweet orange cultivar Pusa Sharad grafted on various citrus rootstocks under sodium chloride stress - Kripa Shankar; Om Prakash Awasthi; Supradip Saha; Jai Prakash; Renu Pandey; Theivanai Murugan; Aria Dolatabadian (Plant Stress)
Rootstock as grafting material mitigates sodium chloride (NaCl) stress by altering physiological, metabolite, and gene expression patterns across different genotypes, cultivars, or species. In this study, we investigated the antioxidant and metabolic responses of sweet orange cultivar Pusa Sharad (PS) grafted onto various rootstocks: Jatti Khatti (JK), X–639 (X9), CRH–12 (C12), NRCC–1 (N1), NRCC–2 (N2), NRCC–3 (N3), NRCC–4 (N4), NRCC–5 (N5), Troyer citrange (TC), CRH–47 (C47), and Cleopatra mandarin (CM). These responses were assessed under different salinity stress levels. Biochemical parameters, including sugars, proline, phenol, soluble protein, hydrogen peroxide (H2O2), superoxide radicals (O2–), lipid peroxidation, catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione reductase (GR), peroxidase (POD), vitamin C, vitamin E, organic acids, and fatty acids were analysed. Results demonstrated that the accumulation of H2O2, O2–, and malondialdehyde (MDA) was upregulated in PS grafted onto the TC, JK, N2, and C12 rootstocks. Conversely, the CAT, SOD, APX, vitamin C, and vitamin E contents were notably higher in PS grafted onto CM, X9, and C47 under 60 mM NaCl stress. Metabolomic analysis indicated that trehalose, raffinose, sucrose, D-galactose, myo-inositol, piperazine, acetic acid, malonic acid, palmitic acid, stearic acid, and pentanoic acid played crucial roles in metabolic adjustments under increasing NaCl stress. Furthermore, PS grafted onto CM, C47, X9, N1, or N3 showed greater tolerance to NaCl compared to those grafted onto JK, C12, N2, N4, N5, or TC, making these combinations adaptable upto 60 mM NaCl concentrations. This study highlights the role of potential metabolites and its use in enhancing NaCl tolerance through grafting onto tolerant rootstocks.